Penanaman Sikap Toleransi Dalam Pembelajaran Ilmu Pengetahuan Sosial di Madrasah Tsanawiyah Baiturrahman Tapung - Istiqomah Wulan Rahmadani; Kusnadi Kusnadi; Sakilah Sakilah; Indah Wati; Alimuddin Alimuddin; Wardani Purnama Sari (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
This study aimed to examine (1) the methods of instilling tolerance attitudes and (2) the factors influencing the cultivation of tolerance in Social Science learning at Islamic Junior High School (MTs) Baiturrahman Tapung. The research was motivated by the lack of tolerance among students. A qualitative approach was employed, with data collected through observation, interviews, and documentation. Data analysis used qualitative descriptive techniques, supported by data validity checks and triangulation. The findings revealed that tolerance was fostered in eighth-grade students through school culture integration, including: (1) greetings in various languages and cultures, (2) forming discussion groups, (3) promoting respectful communication, (4) cultural exchange activities, and (5) celebrating significant religious and cultural events. Additionally, Social Science learning reinforced tolerance by (1) incorporating tolerance values into lesson plans and syllabi, and (2) connecting tolerance attitudes to learning approaches and subject matter. Supporting factors included teacher competence, curriculum design, learning materials, and evaluation methods. Conversely, obstructing factors involved parents' lack of awareness regarding the importance of tolerance. This study highlights the role of educational strategies and school culture in nurturing tolerance, emphasizing the need for collaboration between educators and parents to strengthen students' tolerance attitudes effectively.